2006
DOI: 10.1080/17290376.2006.9724862
|View full text |Cite
|
Sign up to set email alerts
|

Social support and health behaviour in women living with HIV in KwaZulu-Natal

Abstract: The article explores the relationship between social support and health behaviour of rural and urban women who are living with HIV in South Africa. Our study was a descriptive survey of a group of pregnant and non-pregnant women living with HIV. The sample size was 262 women, 165 from urban area and 97 from rural area. Data were collected using 3 instruments, namely a demographic questionnaire, the health behaviour schedule and the Medical Outcomes Study (MOS) Social Support Survey. Significant findings indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…The WHO has promoted peer support groups for those suffering from HIV to reduce stigma and discrimination and to encourage disclosure and help patients adhere to treatment and remain in care 38–40. Attending support groups has even been correlated positively with an increase in condom use and reduced HIV transmission rate 41. A study conducted in Mozambique found a significant increase in the proportion of patients who continued to actively remain in medical care receiving ART 42.…”
Section: Global Health Problem Analysismentioning
confidence: 99%
“…The WHO has promoted peer support groups for those suffering from HIV to reduce stigma and discrimination and to encourage disclosure and help patients adhere to treatment and remain in care 38–40. Attending support groups has even been correlated positively with an increase in condom use and reduced HIV transmission rate 41. A study conducted in Mozambique found a significant increase in the proportion of patients who continued to actively remain in medical care receiving ART 42.…”
Section: Global Health Problem Analysismentioning
confidence: 99%
“…Based on previous studies using the MOS Social Support Survey, including a published study of HIV-positive women, the total score of the MOS Social Support Survey was converted to a 0-100 scale, with very low support defined as a score of 25%, low as 26%-50%, medium as 51%-75%, and high as >76% on the overall functional support index. [17][18][19] Depressive symptoms. The CES-D 10 is a 10-item survey that asks how often respondents have felt a certain way during the past year, with responses on a scale from All of the time to Not at all, for example: I felt depressed.…”
Section: Surveymentioning
confidence: 99%
“…We used several existent instruments with established reliability and validity: the MOS Social Support Survey, [17][18][19] the Center for Epidemiologic Studies Short Depression Scale (CES-D 10), 20 and an expanded version of a previously validated partner violence scale, 21 which also queried emotional abuse.…”
Section: Surveymentioning
confidence: 99%
“…Such networks may also provide avenues for exchange of information, which may help in shaping community norms and become role models for healthy behaviour. A study by Gaede, Majeke, Modeste, Naidoo, Titus and Uys (2006) found an association between good social support, increased use of condoms and vitamin intake.…”
Section: Social Capital and Hiv Transmissionmentioning
confidence: 99%